Factors Affecting Egg Production in Backyard Chicken Flocks - J.P. Jacob; H.R. Wilson; R.D. Miles; G.D. Butcher; F.B. Mather (EDIS)
This document is about the various factors that influence egg production in backyard chicken flocks. It outlines both noninfectious and infectious causes of reduced productivity, including nutritional deficiencies, environmental stressors, parasites, diseases, and management practices. The guide provides practical insights for identifying and addressing issues that may lead to a decline in egg output, helping poultry keepers maintain healthy and productive flocks. Original publication date April 1998.